Routine pathological evaluation of tissue from inguinal hernias in children is unnecessary - Miller, Grant G. (Canadian Medical Association, 2003)
INTRODUCTION: Because unexpected disease is rare in a child's inguinal hernia sac we decided to investigate the cost of routine pathological evaluation of inguinal hernial sacs in children and the incidence of clinically significant pathological findings. METHODS: We searched the health records at the University Hospital, Saskatoon, for patients under 20 years of age who had inguinal hernia repair between 1988 and 1997. For records noting pathology findings of duct-like structures, the operative reports and histology slides were reviewed. Specimens were immunostained for muscle-specific actin. The cost of pathological evaluation was estimated using a provincial physician-billing schedule. RESULTS: During the study period, there were 488 inguinal hernia repairs in 371 patients under 20 years of age. Of these, 456 (93.4%) specimens were evaluated microscopically. There were 4 (0.88%) cases with unexpected findings diagnosed as epididymis at a cost of Can$6988/case. CONCLUSION: The routine histologic evaluation of inguinal hernia sacs in children is an unnecessary expense and should be reserved for select cases at the discretion of the surgeon.